2020
DOI: 10.1021/acsaem.0c01647
|View full text |Cite
|
Sign up to set email alerts
|

Impact of PSBpin Content on the Electrochemical Properties of PTMA-PSBpin Copolymer Cathodes

Abstract: The class of radical polymers is one of the most appealing electrode materials in organic radical batteries (ORBs). Herein, we report a series of copolymers poly(2,2,6,6-tetramethylpiperidinyloxyl-4-yl methacrylate)-poly(4-pinacolatoborylstyrene) (PTMA-PSBpin-n, n = 1, 2, and 3) and explore their electrochemical properties as cathodes for ORBs. At 50 wt % active material content, the PTMA-PSBpin electrodes are found to bear great capacity, long-term cycle life, and impressive rate performance. In addition, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Electrolytes make another essential contribution to the redox processes of radical polymers. Electrolyte counterions must electrically neutralize charged cations or anions formed by redox reactions. Although regular electrolyte ions diffuse more quickly ( D phys ≈10 –7 cm 2 /s in polyelectrolyte gels) , than the electron-hopping diffusion in radical polymer gels ( D et ≈10 –10 cm 2 /s), the neutralization affects charge transport drastically. For instance, a redox peak of a TEMPO-substituted polymer can be split into two peaks by different anion (cation) insertion or expulsion processes. ,, Further study is needed to reveal the relationships among molecular chain movement, electrolyte diffusion, and electron transfer.…”
Section: Redox Processes Of Organic Robust Radicals and Their Polymersmentioning
confidence: 99%
“…Electrolytes make another essential contribution to the redox processes of radical polymers. Electrolyte counterions must electrically neutralize charged cations or anions formed by redox reactions. Although regular electrolyte ions diffuse more quickly ( D phys ≈10 –7 cm 2 /s in polyelectrolyte gels) , than the electron-hopping diffusion in radical polymer gels ( D et ≈10 –10 cm 2 /s), the neutralization affects charge transport drastically. For instance, a redox peak of a TEMPO-substituted polymer can be split into two peaks by different anion (cation) insertion or expulsion processes. ,, Further study is needed to reveal the relationships among molecular chain movement, electrolyte diffusion, and electron transfer.…”
Section: Redox Processes Of Organic Robust Radicals and Their Polymersmentioning
confidence: 99%
“…16,17 In our recent studies, two boron-containing polymer LIB electrodes have shown good electrochemical stability, including a radical material, PTMA-PSBpin, and a quinone-based material, B-AQ. 18,19 The electron energy levels can be effectively adjusted by the introduction of organoboron units, heightening the electron transport characteristics and improving the charge-discharge redox activity of the battery.…”
Section: Introductionmentioning
confidence: 99%
“…22 In our recent studies, the boron-containing radical material PTMA-PSBpin and the quinone-based boron-containing material B-AQ have been prepared, and both have shown good electrochemical stability. 23,24 The incorporation of organoboron units effectively adjusts electron energy levels, enhances electron transport characteristics, and improves electrode redox activity. This motivates us to further explore the performance of novel boroncontaining electrode materials for LIBs.…”
Section: Introductionmentioning
confidence: 99%